Factors influencing the ovarian response in intracytoplasmic sperm injection (ICSI) - Seyed Gholam Ali Jorsaraei; Maryam Gholamitabar Tabari; Yousef reza yousefnia pasha; Mahtab Zeinalzadeh; Ali asghar Beiky; Mahmod Hajiahmadi (Babol University of Medical Sciences, 2017)
Background: Ovarian response to gonadotropin stimulation can predict the success rate of Assisted Reproductive Technology. The purpose of this study was not only to determine the ovarian response rate in patients on whom intracytoplasmic sperm injection (ICSI) did not successfully work but also to assess the influence of factors on ovarian response. Methods: In a retrospective study, the medical records of 220 women undergoing their first cycle of ICSI from March 2012 to October 2016 were thoroughly examined. Special attention was paid to ovarian response with regards to age, body mass index, the history of menstrual cycle, the type of infertility, the duration of infertility, and the cause of infertility with respect to measures of women's hormones. The ovarian response expressing the number of mature MII oocytes after oocyte retrieval was regarded as "poor response" representing a yield of 1-4 oocytes, and "appropriate response" representing a yield of 5 or more oocytes. Results: Out of 220 infertile women, 45 subjects (20.5%) had poor response, 175 subjects (79.5%) had appropriate response to ovulation stimulation with gonadotropin. The results of indicated that lower female age (p=0.005) and lower female FSH (p=0.006) were consistent with appropriate ovarian response. After adjusting the variables, the age (age <30 years) (OR= 2.45, 95% CI= 1.19-5.07) and the female FSH (FSH <30 years) (OR= 2.59, 95% CI= 1.16-5.71) were found to be associated with an appropriate ovarian response. Conclusion: It can be concluded that entering the first cycle of ICSI with FSH test and considering the age of women seem to be acceptable strategies.